2009
DOI: 10.1007/s11104-009-9970-8
|View full text |Cite
|
Sign up to set email alerts
|

Diazotrophic diversity, nifH gene expression and nitrogenase activity in a rice paddy field in Fujian, China

Abstract: The diazotrophic communities in a rice paddy field were characterized by a molecular polyphasic approach including DNA/RNA-DGGE fingerprinting, real time RT-PCR analysis of nifH gene and the measurement of nitrogen fixation activities. The investigation was performed on a diurnal cycle and comparisons were made between bulk and rhizosphere / root soil as well as between fertilized / unfertilized soils. Real time RT-PCR showed no significant difference in the total quantity of nifH expression under the conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 47 publications
2
34
0
Order By: Relevance
“…PCR amplifications of the nifH gene were performed using the universal primers PolF/PolR (Poly et al, 2001) that cover most of the known diazotrophic organisms (Bacteria and Archaea), including cyanobacteria (Mårtensson et al, 2009;Díez et al, 2012). These primers amplify fragments 360 bp in length.…”
Section: Bacterial Nifh Gene Clone Librarymentioning
confidence: 99%
“…PCR amplifications of the nifH gene were performed using the universal primers PolF/PolR (Poly et al, 2001) that cover most of the known diazotrophic organisms (Bacteria and Archaea), including cyanobacteria (Mårtensson et al, 2009;Díez et al, 2012). These primers amplify fragments 360 bp in length.…”
Section: Bacterial Nifh Gene Clone Librarymentioning
confidence: 99%
“…Therefore, we used a culture-independent approach, based on PCR amplification and sequencing of nifH DNA (18,19), to assess the diversity of potential diazotrophs associated with switchgrass. nifH has been used by many researchers to study total and functional diversity of bacteria in various environments (15,(20)(21)(22), and phylogenies based on nifH and 16S rRNA generally are congruent (23,24). Additionally, PCR amplification of cDNA derived from nifH RNA was used to determine whether any bacteria express this gene in association with switchgrass.…”
mentioning
confidence: 99%
“…The former occurs as an intracellular endosymbiont in the gills of marine bivalves which provide host with enzyme including cellulases and nitrogenase critical for nitrogen deficiency [2,18,44,84,85]. While the latter, Azotobacter, is a free living diazotrophic bacteria with metabolic capabilities including atmospheric nitrogen fixation by conversion to ammonia and have a unique system of distinct nitrogenase enzyme [2,35,36,37,44,54].…”
Section: Gammaproteobacteria Groups Is Closely Affiliated Withmentioning
confidence: 99%
“…The diversity of cyanobacterial mats inhabiting different environments have been the focus of numerous studies on the several places such as: Tikehau atoll-French Polynasia [1,66], in New Caledonia [8,9], and in the Western Indian Ocean in Zanzibar-Tanzania [4]. These studies identified different structures which differs in appearance [56], species composition, mode of growth and affiliation to the benthic organism including the coral and their substrate. Thus, these types of bacteria are vital during calcification and decalcification process [8,9], much, in the stability of coralalgae symbosis [32,33,63,76,77].…”
Section: Gammaproteobacteria Groups Is Closely Affiliated Withmentioning
confidence: 99%
See 1 more Smart Citation